Intrinsic Quality Assessment of Arguments - Wachsmuth, Henning; Werner, Till (Proceedings of COLING 2020, the 28th International Conference on Computational Linguistics)

Analyzing the Persuasive Effect of Style in News Editorial Argumentation - El Baff, Roxanne; Wachsmuth, Henning; Al-Khatib, Khalid; Stein, Benno (Proceedings of 58th Annual Meeting of the Association for Computational Linguistics)

Extractive Snippet Generation for Arguments - Alshomary, Milad; Düsterhus, Nick; Wachsmuth, Henning (Proceedings of 43rd International ACM SIGIR Conference on Research and Development in Information Retrieval)

End-to-End Argumentation Knowledge Graph Construction - Al-Khatib, Khalid; Hou, Yufang; Wachsmuth, Henning; Jochim, Charles; Bonin, Francesca; Stein, Benno (Proceedings of the Thirty-Fourth AAAI Conference on Artificial Intelligence (AAAI 2020))

Touché: First Shared Task on Argument Retrieval - Bondarenko, Alexander; Hagen, Matthias; Potthast, Martin; Wachsmuth, Henning; Beloucif, Meriem; Biemann, Chris; Panchenko, Alexander; Stein, Benno (Proceedings of the 42nd European Conference on Information Retrieval (ECIR 2020))

Investigating Expectations for Voice-based and Conversational Argument Search on the Web - Kiesel, Johannes; Lang, Kevin; Wachsmuth, Henning; Hornecker, Eva; Stein, Benno (Proceedings of the 2020 ACM SIGIR Conference on Human Information Interaction & Retrieval (CHIIR 2020))

Visual Analysis of Argumentation in Essays - Kiesel, Dora; Riehmann, Patrick; Wachsmuth, Henning; Stein, Benno; Fröhlich, Bernd (IEEE Transactions of Visualization & Computer Graphics)

Analyzing Political Bias and Unfairness in News Articles at Different Levels of Granularity - Chen, Wei-Fan; Al-Khatib, Khalid; Wachsmuth, Henning; Stein, Benno (Proceedings of the Fourth Workshop on Natural Language Processing and Computational Social Science)

Task Proposal: Abstractive Snippet Generation for Web Pages - Syed, Shahbaz; Chen, Wei-Fan; Hagen, Matthias; Stein, Benno; Wachsmuth, Henning; Potthast, Martin (Proceedings of the 13th International Conference on Natural Language Generation (INLG 2020))

Detecting Media Bias in News Articles using Gaussian Bias Distributions - Chen, Wei-Fan; Al-Khatib, Khalid; Stein, Benno; Wachsmuth, Henning (Findings of the Association for Computational Linguistics: EMNLP 2020)

Abstractive Snippet Generation - Chen, Wei-Fan; Syed, Shahbaz; Stein, Benno; Hagen, Matthias; Potthast, Martin (Proceedings of the Web Conference 2020)

Target Inference in Argument Conclusion Generation - Alshomary, Milad; Syed, Shahbaz; Potthast, Martin; Wachsmuth, Henning (Proceedings of 58th Annual Meeting of the Association for Computational Linguistics (ACL 2020))

Argument Search: Assessing Argument Relevance - Potthast, Martin; Gienapp, Lukas; Euchner, Florian; Heilenkötter, Nick; Weidmann, Nico; Wachsmuth, Henning; Stein, Benno; Hagen, Matthias (42nd International ACM Conference on Research and Development in Information Retrieval (SIGIR 2019))

Book Review: Argumentation Mining - Wachsmuth, Henning (Computational Linguistics)

Data Acquisition for Argument Search: The args.me Corpus - Ajjour, Yamen; Wachsmuth, Henning; Kiesel, Johannes; Potthast, Martin; Hagen, Matthias; Stein, Benno (Proceedings of the 42nd Edition of the German Conference on Artificial Intelligence)

Modeling Frames in Argumentation - Ajjour, Yamen; Alshomary, Milad; Wachsmuth, Henning; Stein, Benno (Proceedings of the 2019 Conference on Empirical Methods in Natural Language Processing and 9th International Joint Conference on Natural Language Processing)

Proceedings of the 6th Workshop on Argument Mining

Computational Argumentation Synthesis as a Language Modeling Task - El Baff, Roxanne; Wachsmuth, Henning; Al-Khatib, Khalid; Stede, Manfred; Stein, Benno (Proceedings of the 12th International Conference on Natural Language Generation)

Wikipedia Text Reuse: Within and Without - Alshomary, Milad; Völske, Michael; Licht, Tristan; Wachsmuth, Henning; Stein, Benno; Hagen, Matthias; Potthast, Martin (Advances in Information Retrieval)
We study text reuse related to Wikipedia at scale by compiling the first corpus of text reuse cases within Wikipedia as well as without (i.e., reuse of Wikipedia text in a sample of the Common Crawl). To discover reuse beyond verbatim copy and paste, we employ state-of-the-art text reuse detection technology, scaling it for the first time to process the entire Wikipedia as part of a distributed retrieval pipeline. We further report on a pilot analysis of the 100 million reuse cases inside, and the 1.6 million reuse cases outside Wikipedia that we discovered. Text reuse inside Wikipedia gives rise to new tasks such as article template induction, fixing quality flaws, or complementing Wikipedia's ontology. Text reuse outside Wikipedia yields a tangible metric for the emerging field of quantifying Wikipedia's influence on the web. To foster future research into these tasks, and for reproducibility's sake, the Wikipedia text reuse corpus and the retrieval pipeline are made freely available.

Unraveling the Search Space of Abusive Language in Wikipedia with Dynamic Lexicon Acquisition - Chen, Wei-Fan; Al-Khatib, Khalid; Hagen, Matthias; Wachsmuth, Henning; Stein, Benno (Proceedings of the Second Workshop on Natural Language Processing for Internet Freedom)